Visual Improvement Following Glaucoma Surgery: Poster Presentation - Case Report - Ophthalmologist - Purnamasari, Heronita (Majalah Oftalmologi Indonesia, 2023)
Introduction : Glaucoma is a progressive optic neuropathy and a leading cause of irreversible blindness. The aim of glaucoma treatment is to slow progression and minimize the risk of further damage, not to expect functional improvement. We report the case of a patient who experienced an improvement in vision following glaucoma surgery and review the literature regarding this phenomenon. Case Illustration : A 66-year old female presented with vision loss in the left eye that could only perceive finger counting in one meter. Her intraocular pressure (IOP) measured 51,8 mmHg and she was found to have primary open angle glaucoma. Medical treatment was commenced and she underwent a successful trabeculectomy. Unexpectedly she experienced improvement in vision after treatment. At her recent visit visual acuity was 6/30 in the affected eye. Discussion : Although the mechanism of improved vision cannot be proven it is likely that successful lowering of IOP resulted in some reversal of retinal ganglion cell dysfunction. Some evidence explained that retinal ganglion cells damaged by glaucoma might undergo a period of reversible dysfunction preceding cell death. Furthermore, reversible changes in optic nerve head morphology have been reported following reduction of intraocular pressure. These observations suggest that certain structural and functional improvements may in fact be possible in some patients. The changes of anterior chamber depth, corneal radius of curvature, corneal thickness or corneal edema could be considered as other factors which influence this improvement. Conclusion : Functional improvements may occur following trabeculectomy. Glaucoma surgery should be offered early, and considered even in those with reduced visual acuity.